2020
DOI: 10.1016/j.radonc.2020.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a deep learning algorithm for auto-delineation of clinical target volume and organs at risk in cervical cancer radiotherapy

Abstract: The delineation of the clinical target volume (CTV) is a crucial, laborious and subjective step in cervical cancer radiotherapy. The aim of this study was to propose and evaluate a novel end-to-end convolutional neural network (CNN) for fully automatic and accurate CTV in cervical cancer. Methods: A total of 237 computed tomography (CT) scans of patients with locally advanced cervical cancer were collected and evaluated. A novel 2.5D CNN network, called DpnUNet, was developed for CTV delineation and further ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 33 publications
1
64
1
Order By: Relevance
“…Our group also previously demonstrated the potential of deep learning-based autosegmentation of target volumes and OARs in breast cancer radiotherapy [ 7 , 8 ]. A training set for a proposed deep learning-based autocontouring system (ACS) is generally generated by a single expert or a small group of experts [ 9 ]. Therefore, generalization is often discussed as an issue of external validity.…”
Section: Introductionmentioning
confidence: 99%
“…Our group also previously demonstrated the potential of deep learning-based autosegmentation of target volumes and OARs in breast cancer radiotherapy [ 7 , 8 ]. A training set for a proposed deep learning-based autocontouring system (ACS) is generally generated by a single expert or a small group of experts [ 9 ]. Therefore, generalization is often discussed as an issue of external validity.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model is based on DpnUNet ( 13 ), which originated from the architecture of U-Net ( 19 ), but replaces all the encoder and decoder components with DPN components. Considering that the original DpnUNet is still underperforming compared with manual delineation in clinical practice, an extra convolutional layer is added at the end of DpnUNet, in which the output channels are one and the kernel size is 1 × 1.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has first applied a deep-learning-based method called DpnUNet to CTV segmentation in cervical cancer. The authors’ previous experimental results demonstrated that 88.65% of the contours generated by DpnUNet were acceptable for clinical usage ( 13 ). The mean dice similarity coefficient (DSC) and the 95 th Hausdorff distance (95HD) were 0.86 and 5.34 for the delineated CTVs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potentials of artificial intelligence (AI) in healthcare to automatize, standardize and speed-up processes has been discussed extensively [2][3][4][5][6]. In RT, the automation of single workflow steps has recently been investigated by several groups, especially with respect to automatic contouring and plan optimization [7][8][9][10][11][12][13][14][15][16]. For automatic segmentation of organs at risk (OAR), deep learning (DL)-based solutions showed promising results, with first reports on introduction into clinical routine and commercialization [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…In RT, the automation of single workflow steps has recently been investigated by several groups, especially with respect to automatic contouring and plan optimization [7][8][9][10][11][12][13][14][15][16]. For automatic segmentation of organs at risk (OAR), deep learning (DL)-based solutions showed promising results, with first reports on introduction into clinical routine and commercialization [7][8][9][10][11][12]. Solutions for automatic treatment plan optimization were developed and are today partly available for routine planning in commercial treatment planning systems (TPS) [13][14][15][16].…”
mentioning
confidence: 99%